PENERAPAN ALAT PERAGA IPAS DIOROMA UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI RANTAI MAKANAN DI KELAS Vb SD NEGERI 2 TIAKUR - Ridolfina Unawekla; Renny Souhoka; Ince Wattimury (STKIP Subang, 2025)
This study aims to investigate the implementation of IPAS teaching aids in the form of dioramas to improve students’ learning outcomes on the topic of food chains in class Vb of SD Negeri 2 Tiakur. The research employed a classroom action research (CAR) method conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects were 25 fifth-grade students. Data were collected through learning achievement tests, student activity observations, and documentation. The results showed that the use of dioroma teaching aids in IPAS learning enhanced students’ understanding of the food chain concept. The average student score increased from 67.2 in the pre-cycle to 78.4 in cycle I and 87.6 in cycle II. Students’ learning activities also showed significant improvement. Therefore, it can be concluded that the implementation of IPAS diorama teaching aids is effective in improving students’ learning outcomes on the topic of food chains in class Vb of SD Negeri 2 Tiakur.